Prospective assessment of pre-existing and de novo anti-HLA IgE in kidney, liver, lung and heart transplantation - Mucha, Jasmin; Cho, Ara; Weijler, Anna Marianne; Muckenhuber, Moritz; Hofmann, Amun Georg; Wahrmann, Markus; Heinzel, Andreas; Linhart, Birgit; Gattinger, Pia; Valenta, Rudolf; Berlakovich, Gabriela; Zuckermann, Andreas; et al. (Frontiers in Immunology, 2023)
Antibody mediated rejection (ABMR) is a major factor limiting outcome after organ transplantation. Anti-HLA donor-specific antibodies (DSA) of the IgG isotype are mainly responsible for ABMR. Recently DSA of the IgE isotype were demonstrated in murine models as well as in a small cohort of sensitized transplant recipients. In the present study, we aimed to determine the frequency of pre-existing and de novo anti-HLA IgE antibodies in a cohort of 105 solid organ transplant recipients. We prospectively measured anti-HLA IgE antibodies in a cohort of kidney (n=60), liver, heart and lung (n=15 each) transplant recipients before and within one-year after transplantation, employing a single-antigen bead assay for HLA class I and class II antigens. Functional activity of anti-HLA IgE antibodies was assessed by an in vitro mediator release assay. Antibodies of the IgG1-4 subclasses and Th1 and Th2 cytokines were measured in anti-HLA IgE positive patients. Pre-existing anti-HLA IgE antibodies were detected in 10% of renal recipients (including 3.3% IgE-DSA) and in 4.4% of non-renal solid organ transplant recipients (heart, liver and lung cohort). Anti-HLA IgE occurred only in patients that were positive for anti-HLA IgG, and most IgE positive patients had had a previous transplant. Only a small fraction of patients developed de novo anti-HLA IgE antibodies (1.7% of kidney recipients and 4.4% of non-renal recipients), whereas no de novo IgE-DSA was detected. IgG subclass antibodies showed a distinct pattern in patients who were positive for anti-HLA IgE. Moreover, patients with anti-HLA IgE showed elevated Th2 and also Th1 cytokine levels. Serum from IgE positive recipients led to degranulation of basophils in vitro, demonstrating functionality of anti-HLA IgE. These data demonstrate that anti-HLA IgE antibodies occur at low frequency in kidney, liver, heart and lung transplant recipients. Anti-HLA IgE development is associated with sensitization at the IgG level, in particular through previous transplants and distinct IgG subclasses. Taken together, HLA specific IgE sensitization is a new phenomenon in solid organ transplant recipients whose potential relevance for allograft injury requires further investigation.